A Comparison of Proposals to Restructure the U.S. Financial System - R. Alton Gilbert (Levy Economics Institute of Bard College, 1993)
This paper illustrates the potential for risk diversification through the common ownership of a hypothetical bank and nonbanking firm. The illustration has several implications for proposals for restructuring the financial system. Banks are not necessarily made safer by requiring that all nonbanking activities be conducted through separate subsidiaries. On the contrary, banks may be less vulnerable to failure if some nonbanking activities are offered through the banks directly. Moreover, the expected loss of federal deposit insurance funds may be lower even if the nonbanking activities are financed through insured deposits. The major proposals for restructuring the financial system would permit firms in various industries to buy banks and operate them as separate subsidiaries. Some of the proposals build in safeguards to prevent nonbanking firms from using the resources of their bank subsidiaries in ways that would increase both the chance for bank failure and the expected loss of the federal deposit insurance funds. These restrictions are based on the presumption that, without such safeguards, nonbanking firms would use the resources of their bank subsidiaries to benefit their nonbank subsidiaries.
Keywords: 330